Wind turbine wake calculation model with exponential reciprocal attenuation. (June 2022) - Ren, Jianhua; Niu, Wang; Liu, HongYu
This paper studies the general wind turbine wake mathematical model—Jensen model based on some famous wind tunnel experimental data. Based on the study of the initial Jensen wake model equation, the improved semi empirical Jensen model equation was studied in this paper considering the factors of wind turbine wake attenuation in the distance. According to the form of exponential reciprocal attenuation, the model was modified again. Corresponding Jensen exponential reciprocal attenuation wake model was obtained. The simulations and contrast experiments were carried out in the advanced calculation tool. Corresponding comparison experiments of various wake equations were carried out. The theoretical and experimental results show that Jensen exponent reciprocal attenuation wake model can accurately calculate the variation of general wind turbine wake. Its development and application have important theoretical significance and practical value for wind energy utilization.